Passing the Baton Conductors and the Royal Ballet - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2008)
In October 2008, Covent Garden introduced intake of Jette Parker Young Artists (JPYA) at a concert in the Lindury Theatre. For the first time they include a nominee from the Royal Ballet, the conductor Dominic Grier.